Membrane Stabilizing Potency of Two Tephrosia Species - Vinod1, R.K. Chaitanya1, J. Chandrasekhar1, K. Sudhakar1; T. Rajeswar1, S. Sandhya1*, K. Venkatramana2, K.R. (Journal of Phytology, 2010)
SUMMARY Tephrosia maxima and Tephrosia purpurea Pers. is a pan tropical coastal shrub which contain flavonoids and isoflavanones. Since flavonoids exhibit good anti inflammatory activity an attempt has been made to evaluate its invitro anti inflammatory activity by means of HRBC membrane stabilizing method on three chloroform, ethyl acetate and methanolic extracts of the root of both the plants to identify the potent extract. The preliminary chemical tests revealed that all the extracts contain tannins and flavonoids. In the methanolic extract of both the plants presence of saponins was detected. In the invitro anti inflammatory activity screening it was observed that all the three extracts of both the plants showed significant HRBC membrane stabilization activity with regard to the standard hydrocortisone of 88.2% at 500 μg/ml. The methanolic extract of the plants was found be a better choice with a percentage protection of 79.49% and 79.01% at 500 μg/ml for Tephrosia maxima and Tephrosia purpurea respectively. Key words: Tephrosia maxima, Tephrosia purpurea, Alsever solution, HRBC membrane stabilization <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Sandhya S et al. Membrane Stabilizing Potency of Two Tephrosia Species. J Phytol 2/6 (2010) 42-46